PENERAPAN METODE TUTOR SEBAYA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA SEKOLAH DASAR - Febrizal Hidayat; Neni Mariana; Vivie Shintawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to increase student learning motivation by using the peer tutoring method and describe the improvements. This research is classroom action research with the subject of 29 fifth grade elementary school students at one of the State Elementary Schools in Surabaya. Data was collected through observation and questionnaires. The research results show that the peer tutoring method is effective in increasing students' learning motivation in Mathematics subjects, especially in multiplication and division of fractions. The increase in motivation can be seen from the achievement of student learning motivation which was initially 31% in the pre-cycle, increased to 72% in cycle I, and reached 97% in cycle II. Based on these results, the level of achievement of learning motivation is in the very good category, so that the implementation of the action is declared successful.